The validity of diagnostic cut-offs for commercial and in-house scrub typhus IgM and IgG ELISAs: A review of the evidence - Saraswati, Kartika (PLoS Negl Trop Dis, 2019)
BACKGROUND: Scrub typhus is a neglected tropical disease that causes acute febrile illness. Diagnosis is made based upon serology, or detection of the causative agent–Orientia tsutsugamushi–using PCR or in vitro isolation. The enzyme-linked immunosorbent assay (ELISA) is an objective and reproducible means of detecting IgM or IgG antibodies. However, lack of standardization in ELISA methodology, as well as in the choice of reference test with which the ELISA is compared, calls into question the validity of cut-offs used in diagnostic accuracy studies and observational studies. METHODOLOGY/PRINCIPAL FINDINGS: A PubMed search and manual screening of reference lists identified 46 studies that used ELISA antibody cut-offs to diagnose scrub typhus patients, 22 of which were diagnostic accuracy studies. Overall, 22 studies (47.8%) provided little to no explanation as to how the ELISA cut-off was derived, and 7 studies (15.2%) did not even state the cut-off used. Variation was seen locally in reference standards used, in terms of both the diagnostic test and cut-off titer. Furthermore, with the exception of studies using ELISAs manufactured by InBios, there was no standardization of the selection of antigenic strains. As a result, no consensus was found for determining a cut-off, ELISA methodology, or for a single value diagnostic cut-off. CONCLUSIONS/SIGNIFICANCE: We have concluded that there is a lack of consensus in the determination of a cut-off. We recommend interpreting the results from these studies with caution. Further studies will need to be performed at each geographic location to determine region-specific cut-offs, taking into consideration background antibody levels to discriminate true disease from healthy individuals.